2005
DOI: 10.1097/00124784-200507000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Tuberculosis Treatment Interruption in New York City

Abstract: Efforts to improve patients' understanding of TB disease and related treatment issues may be an important TB control program strategy and should be emphasized at the initiation of therapy and at intervals throughout the treatment course to minimize treatment interruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Some studies have reported communication barriers or poor communication between patients and providers as being linked to poor adherence [15,17,18]. Perceived communication quality or lack thereof may reflect the status of the patient provider relationship and influence patient behavior [18,19]. Other studies have reported associations between TB treatment default and a poor level of knowledge of TB or low patient satisfaction regarding information provided concerning their illness [17-20].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported communication barriers or poor communication between patients and providers as being linked to poor adherence [15,17,18]. Perceived communication quality or lack thereof may reflect the status of the patient provider relationship and influence patient behavior [18,19]. Other studies have reported associations between TB treatment default and a poor level of knowledge of TB or low patient satisfaction regarding information provided concerning their illness [17-20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed before that adverse events during treatment increase the risk of non-adherence to therapy [13,20-25]. Driver [26] studied determinants for treatment interruption and found that the lack of TB disease and treatment related knowledge were important reasons for patients discontinuing treatment. Indeed, health education has shown to improve treatment adherence [24].…”
Section: Discussionmentioning
confidence: 99%
“…Different patient groups may also be associated with higher probability of interrupting treatment [6][8]. Further, the methods used to define treatment interruption have not been standard across studies with some defining interruption as any single missed treatment dose [4], [5], [7], utilizing the number of times treatment was interrupted [4], the median or total duration of missed doses [5], [6], maximum number of consecutive doses missed [4], [7], or cut-offs for proportion of total treatment that was missed [6], [8]. It is possible that some crude definitions lack sensitivity to identify patients at greatest risk for poor outcomes; other categorizations may have differing relevance to outcomes within a program context.…”
Section: Introductionmentioning
confidence: 99%